PENGARUH MODEL PJBL TERHADAP KEMAMPUAN BERPIKIR KREATIF SISWA SD PADA MATA PELAJARAN IPAS - Jihan Nur Fadhilah; Yoyo Zakaria Ansori; Yeni Dwi Kurino (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study examines students’ creative thinking skills in the IPAS subject using the Project Based Learning (PjBL) model in Grade V. The purpose of this study was to determine the difference in the effect of the PjBL model on creative thinking skills compared to conventional learning models. This research employed a quantitative approach with a quasi-experimental design of the non-equivalent control group type. The population consisted of all Grade V students at SDN Maja Selatan VI, with a sample of 39 students, comprising 20 students in the experimental class and 19 students in the control class. The normality test results showed significance values of 0.074 > 0.05 for the experimental class and 0.118 > 0.05 for the control class, indicating that the data were normally distributed. The homogeneity test using Levene’s Test produced a significance value of 0.357 > 0.05, indicating that both groups were homogeneous. The t-test results revealed that the calculated t-value exceeded the critical t-value and the significance value was 0.000 < 0.05, indicating a significant difference in creative thinking skills between the experimental and control classes. Therefore, the application of the PjBL model has a significant effect on improving students’ creative thinking skills in the IPAS subject.